The Effect of Mild Digital Detox Intervention on Students’ Affective Balance - Sekar Ayuningrum, Sekar Ayuningrum (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2025)
In the digital age, students often suffer from mental health problems because they use their smartphones too much, which makes it hard for them to control their emotions and feel good about themselves. The objective of this study was to investigate the efficacy of a digital detox intervention in enhancing emotional regulation and promoting tranquility among university students. Employing a mixed-method approach with a quasi-experimental design, five participants (S1–S5) engaged in a seven-day digital detox program that limited social media and non-essential digital activities. Data were gathered via self-report scales and narrative reflection journals, subsequently analyzed descriptively and thematically. The findings demonstrated substantial enhancements in emotional stability, concentration, and sleep quality, suggesting that diminished screen exposure facilitated psychological equilibrium and inner tranquility. The results show that a digital detox can be a good way to improve mental health, especially for people who are prone to becoming dependent on technology. Additional research involving larger and more heterogeneous samples is necessary to corroborate these findings.